2020
DOI: 10.1186/s41073-019-0088-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of geographic bias in knowledge diffusion: a systematic review and narrative synthesis

Abstract: Background: Descriptive studies examining publication rates and citation counts demonstrate a geographic skew toward high-income countries (HIC), and research from low-or middle-income countries (LMICs) is generally underrepresented. This has been suggested to be due in part to reviewers' and editors' preference toward HIC sources; however, in the absence of controlled studies, it is impossible to assert whether there is bias or whether variations in the quality or relevance of the articles being reviewed expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 35 publications
3
57
0
Order By: Relevance
“…62 A systematic review (three randomised control trials; n=2,568) found geographic bias for research from high-income countries or more prestigious journals over lowincome countries or less prestigious journals. 63 This highlights how publication bias for research from high-income countries could neglect a wealth of data from low-income countries that is valid, even if it is not published, or only published in lower impact journals. These data highlight a greater need for more objective assessments of research, including multiple layers of blinding with a journal review board and peer reviewers from low-income countries.…”
Section: Bias In Research Evidence Synthesis and Policymentioning
confidence: 99%
See 1 more Smart Citation
“…62 A systematic review (three randomised control trials; n=2,568) found geographic bias for research from high-income countries or more prestigious journals over lowincome countries or less prestigious journals. 63 This highlights how publication bias for research from high-income countries could neglect a wealth of data from low-income countries that is valid, even if it is not published, or only published in lower impact journals. These data highlight a greater need for more objective assessments of research, including multiple layers of blinding with a journal review board and peer reviewers from low-income countries.…”
Section: Bias In Research Evidence Synthesis and Policymentioning
confidence: 99%
“…These data highlight a greater need for more objective assessments of research, including multiple layers of blinding with a journal review board and peer reviewers from low-income countries. 63 However, blinding may be beneficial when recruiting people to jobs from job applications given that application photos may influence the selection process at resident or registrar level. 64 It may be difficult to anonymise citations or publication data during academic selection processes.…”
Section: Bias In Research Evidence Synthesis and Policymentioning
confidence: 99%
“…Further, the perceived higher status of universities in the Global North disproportionately draws talented international students to their degree programmes. [17][18][19][20][21][22] We should rethink and indeed disband university rankings, replace authorship positions with statements of contribution, and judge our researchers and educators based on the full range of activities, on October 31, 2020 by guest. Protected by copyright.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Broadly speaking, researchers have raised concerns that author characteristics, such as gender, [10][11][12][13] geographical location, [14][15][16] and institutional affiliation 17,18 can bias publications, including knowledge syntheses, and inadvertently reinforce dominant power structures. To this point, the Cochrane Collaboration, a major supporter and publisher of systematic reviews, has flagged the lack of international representation and diversity in published reviews as a significant problem and reports that more diverse author teams generate more relevant reviews with less research waste and fewer errors.…”
Section: Introductionmentioning
confidence: 99%